Foreshadowing Vesey: the Camden slave conspiracy of 1816. Issue 2 (4th May 2022) - Lockley, Tim
ABSTRACT: The Vesey conspiracy was the largest in North America, yet historians have failed to establish the wider contexts for how white authorities responded to the plot. This article points to a conspiracy in Camden, South Carolina, in 1816 to argue that many of the responses to Vesey derived from participants' knowledge of Camden. In particular, those representing Charleston in the state legislature gained first-hand knowledge of the plot and several later became key actors in the Vesey trials. The Camden conspiracy in 1816 thus established the wider socio-political context for the unfolding of the Vesey trials in 1822.